Synaptic density marker SV2A is reduced in schizophrenia patients and unaffected by antipsychotics in rats - Ellis Chika Onwordi (Nature Portfolio, 2020)
Synaptic dysfunction is hypothesised to play a key role in schizophrenia pathogenesis. Here, using [11C]UCB-J PET, the authors show for the first time in vivo that levels of the synaptic marker protein SV2A are reduced in schizophrenia and unaffected by antipsychotic treatment in a rat model.